Agro-ecological characterization of vermicomposted sewage sludge from municipal and poultry enterprise wastewater treatment plants - Dermendzhieva, Diyana; Dinev, Toncho; Kostadinova, Gergana; Petkov, Georgi; Beev, Georgi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study was to make an agro-ecological characterization of vermicompost (VC) produced from sewage sludge (SS). As a substrate, SS from municipal and poultry meat processing enterprise wastewater treatment plants (MTP and PTP, respectively) was utilized. The substrates were vermicomposted by Red Californian earthworm (Lumbricus rubellus) for 120 days. For VC quality assessment, 19 physicochemical and 6 microbiological parameters were used. The evaluation of physicochemical parameters was done according to ISO standard methods and microbiological analysis-by plating 1 mL of sample dilutions on selective, chromogenic culture medium sheets. It was found that the vermicompost from MTP (VC-M) had higher levels of EC, mineral elements (N, P and K compounds in forms available to plants), heavy metals (Mn, Cu, Zn, Cr, Ni, Pb, Cd) and coliforms, and lower levels of pH, TOC, C/N ratio, Fe, total plate count (TPC), Enterobacteriaceae and Salmonella spp. counts compared to VC from PTP (VC-P). During the vermicomposting process, the substrates from both wastewater treatment plants (TPs) showed similar trends towards decrease in pH, TOC, N-NH4+, C/N ratio, TPC, coliforms, E. coli, Enterobacteriaceae and Salmonella spp. counts, whereas the opposite trends were established for EC, TKN, N-NO3-, TP, P2O5, TK, and K2O values. The vermicomposting had a negligible effect on heavy metal concentrations. In the final substrates E. coli were not detected, while the bacterial spore forms (Clostridium perfringens) were not eliminated. The final substrates cannot be used as fertilizers or soil amendments because of the presence of Salmonella spp. and C. perfringens over the permissible limits according to EU and Bulgarian regulations.